New Insight into a Deceptively Simple Reaction: The Coordination of bpy to RuII–Carbonyl Precursors – The Central Role of the fac‐[Ru(bpy)Cl(CO)3]+ Intermediate and the Chloride Rebound Mechanism. Issue 26 (21st August 2015) - Balducci, Gabriele; Iengo, Elisabetta; Demitri, Nicola; Alessio, Enzo
Abstract: This work demonstrates how a careful reexamination of well‐trodden fields can fill conceptual gaps that previously escaped full understanding. The coordination of 2, 2′‐bipyridine (bpy) to the known Ru II –chlorido–carbonyl precursors – the dinuclear [RuCl2 (CO)3 ]2 (P1 ) and the polymeric [RuCl2 (CO)2 ] n (P2 ) – has been investigated by several groups in the past, and a remarkably large number of ruthenium–mono(bpy)–carbonyl compounds were identified and fully characterized. Many were investigated as catalysts or key intermediates for the photochemical, electrochemical, and photo‐electrochemical reduction of CO2, and for the water–gas shift reaction. Nevertheless, even though most – if not all – of the reaction products are known already, a careful examination of the literature led us to believe that a convincing general scheme interconnecting them all was still missing and important questions remained unanswered. For this reason, we investigated the reactivity of two mononuclear Ru II –carbonyl–dmso precursors, trans, cis, cis ‐[RuCl2 (CO)2 (dmso‐O)2 ] (P3 ) and fac ‐[RuCl2 (CO)3 (dmso‐O)] (P4 ) – which can be considered as "activated forms" ofP2 andP1, respectively – towards the coordination of bpy. CompoundsP3 andP4 allowed us to gain new mechanistic insight and a deeper level of understanding. In particular, we found that coordination of bpy toP4 (orP1 ) generates first the tricarbonyl cation fac ‐[Ru(bpy)Cl(CO)3 ] + . This key intermediate undergoes the facile and selective nucleophilic attack on the CO trans to Cl (by RO – in alcoholic solvents or OH – from adventitious water in other solvents), leading to all other species. We also demonstrated that Cl – – even when in large excess – is unable to replace a carbonyl on fac ‐[Ru(bpy)Cl(CO)3 ] + . However, the chloride set free from the precursor competes efficiently with bpy for the coordination to Ru II ( chloride rebound mechanism). Abstract : This manuscript reinvestigates the coordination of 2, 2′‐bipyridine (bpy) to Ru II –chlorido–carbonyl precursors. A thorough review of the literature data is followed by our original results and a detailed discussion that wraps up old and new results in a comprehensive frame and shows that the coordination of diimines to Ru II –carbonyl precursors has a more complex mechanism than anticipated.